Growth and transcriptional response of wheat and rice to the tertiary amine BMVE - Dharni, Jaspinder Singh; Shi, Yu; Zhang, Chi; Petersen, Chris; Walia, Harkamal; Staswick, Paul (Frontiers in Plant Science, 2024)
Seed vigor is a product of seed development, maturation, genetics and storage conditions, that impacts subsequent plant growth and yield. Seed development and seed vigor are negatively impacted by unfavorable environmental conditions. These vary depending on growing regions but can include drought and heat as well as cold wet conditions. In many parts of the world the later lead to slow germination and increased seedling susceptibility to pathogens. Prior research has shown that a class of plant growth regulators called substituted tertiary amines (STAs) can enhance seed germination, seedling growth, and crop productivity. However, inconsistent benefits have limited STA adoption on a commercial scale. We developed a novel treatment protocol to evaluate the efficacy of 2-(N-methyl benzyl aminoethyl)-3-methyl butanoate (BMVE), which has shown promise as a seed treatment in field trials for multiple crops. BMVE treatment of seeds after 24 h of imbibition consistently improved wheat and rice seedling shoot and root growth in lab conditions. Treated wheat seedlings grown to maturity in a greenhouse also resulted in higher biomass than controls, though only under drought conditions. Transcriptomic analysis of rice seedlings 24 h after BMVE treatment was done to identify the molecular basis for the improved seedling growth. Treated seedlings had increased levels of transcripts involved in reactive oxygen species scavenging and auxin and gibberellic acid signaling. Conversely, several genes associated with increased reactive oxygen species/ROS load, abiotic stress responses, and germination hindering processes were reduced. The impact of BMVE on seed development was also evaluated by spraying rice panicles shortly after flower fertilization and subsequently monitoring the impact on seed traits. BMVE spray increased both fresh and mature seed weights relative to the control for plants exposed to 96 h of heat stress. BMVE treatment during seed development also benefited germination and seedling growth in the next generation, under both ambient and heat stress conditions. The optimized experimental conditions we developed provide convincing evidence that BMVE does indeed have efficacy in plant growth enhancement. The results advance our understanding of how STAs work at the molecular level and provide insights for their practical application to improve crop growth.